2004
DOI: 10.1111/j.1365-2222.2004.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

The flow‐cytometric determination of basophil activation induced by aspirin and other non‐steroidal anti‐inflammatory drugs (NSAIDs) is useful for in vitro diagnosis of the NSAID hypersensitivity syndrome

Abstract: Flowcytometric determinations of basophil activation following stimulation with NSAIDs show a high sensitivity (60-70%) with specificity above 90%. So this test may help avoiding some cumbersome and dangerous provocation challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 42 publications
4
108
2
2
Order By: Relevance
“…Mast cells are the key cell model for urticaria and release histamine and other chemical mediators, which produce urticarial symptoms, 20 and mast cell activation has been reported in ASA-intolerant urticaria patients. 21 Besides, PGE2 could suppress excessive anti-IgE-induced cysteinyl leukotriene production in mast cells in patients with AERD. 12 Our result confirmed that the functional study of PTGER4 promoter polymorphism in HMC-1 cell line showed differential transcriptional regulation by dual-luciferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are the key cell model for urticaria and release histamine and other chemical mediators, which produce urticarial symptoms, 20 and mast cell activation has been reported in ASA-intolerant urticaria patients. 21 Besides, PGE2 could suppress excessive anti-IgE-induced cysteinyl leukotriene production in mast cells in patients with AERD. 12 Our result confirmed that the functional study of PTGER4 promoter polymorphism in HMC-1 cell line showed differential transcriptional regulation by dual-luciferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of cell surface molecule CD63 expression upon in vitro challenge has been proposed for in vitro diagnosis of AERD (35). However, reported specificity and sensitivity were variable, and no firm conclusion could be proposed for the reliability of this test in the routine setting (36).…”
Section: Basophil Activation Test (Bat)mentioning
confidence: 99%
“…37 There is no reliable in vitro diagnostic test for AERD, and, as such, in the absence of a history of aspirin or NSAID use or an ambiguous history of symptoms after exposure, the patient should be referred for aspirin challenge to receive a definitive diagnosis. 1,10,38,39 Diagnostic challenges must be performed without LT modifiers (in contrast to desensitization [as described below]) because these agents can completely mask the symptoms and signs of a reaction. 17,[40][41][42] As such, this diagnostic tool must be used with caution because the expected reaction to aspirin in a patient who is allergic has the potential to induce severe bronchospasm.…”
Section: Diagnosismentioning
confidence: 99%